Identification of long noncoding RNAs involved in resistance to downy mildew in Chinese cabbage. (1st March 2021) - Zhang, Bin; Su, Tongbing; Li, Peirong; Xin, Xiaoyun; Cao, Yunyun; Wang, Weihong; Zhao, Xiuyun; Zhang, Deshuang; Yu, Yangjun; Li, Dayong; Yu, Shuancang; Zhang, Fenglan
Abstract: Brassica downy mildew, a severe disease caused by Hyaloperonospora brassicae, can cause enormous economic losses in Chinese cabbage ( Brassica rapa L. ssp. pekinensis ) production. Although some research has been reported recently concerning the underlying resistance to this disease, no studies have identified or characterized long noncoding RNAs involved in this defense response. In this study, using high-throughput RNA sequencing, we analyzed the disease-responding mRNAs and long noncoding RNAs in two resistant lines (T12–19 and 12–85) and one susceptible line (91–112). Clustering and Gene Ontology analysis of differentially expressed genes (DEGs) showed that more DEGs were involved in the defense response in the two resistant lines than in the susceptible line. Different expression patterns and proposed functions of differentially expressed long noncoding RNAs among T12–19, 12–85, and 91–112 indicated that each has a distinct disease response mechanism. There were significantly more cis - and trans -functional long noncoding RNAs in the resistant lines than in the susceptible line, and the genes regulated by these RNAs mostly participated in the disease defense response. Furthermore, we identified a candidate resistance-related long noncoding RNA, MSTRG.19915, which is a long noncoding natural antisense transcript of a MAPK gene, BrMAPK15 . Via an agroinfiltration-mediated transient overexpression system and virus-induced gene silencing technology, BrMAPK15 was indicated to have a greater ability to defend against pathogens. MSTRG.19915 -silenced seedlings showed enhanced resistance to downy mildew, probably because of the upregulated expression of BrMAPK15 . This research identified and characterized long noncoding RNAs involved in resistance to downy mildew, laying a foundation for future in-depth studies of disease resistance mechanisms in Chinese cabbage.